An eleven-year history of Vanishing White Matter Disease in an adult patient with no cognitive decline and EIF2B5 mutations. A case report. Issue 6 (2nd November 2021) - Trevisan, Lucia; Grazzini, Matteo; Cianflone, Annalia; Accogli, Andrea; Finocchi, Cinzia; Capello, Elisabetta; Saitta, Laura; Grandis, Marina; Roccatagliata, Luca; Mandich, Paola
ABSTRACT: Vanishing White Matter Disease (VWMD) is a rare autosomal recessive leukoencephalopathy . The classical presentation is characterized by a severe cerebellar ataxia, spasticity, neurological deterioration with a chronic progressive course and episodes of acute neurological deterioration after stress conditions. We report a 52-year-old man with VWMD and atypical features who manifested two major events of transient aphasia eleven years apart with complete recovery in 48 hours. No cognitive decline was present. Brain MRI revealed typical aspects of VWMD including diffuse leukoencephalopathy with relative sparing of U-fibers. We identified the presence of c.592G>A (p.Glu198Lys) and c.1360 C>T (p.Pro454Ser) mutations in EIF2B5 .